Overcrowded Warga Binaan Lembaga Pemasyarakatan Kelas II Bsiborongborong Sebab Peningkatan Jumlah Pelaku Narkotika - Rendifa Basita Sembiring (Pusat Riset dan Inovasi Nasional, 2024)
This study discusses the increase in the number of inmates related to the crime of drug abuse and/or illicit trafficking which resulted in overcrowding in the Class IIB Siborongborong Prison. In this regard, it specifically discusses the factors causing the increase in the number of inmates related to the crime of drug abuse and/or illicit trafficking in the Class IIB Siborongborong Prison, the impact of overcrowding in the Class IIB Siborongborong Prison due to the increase in the number of inmates related to the crime of drug abuse and/or illicit trafficking, and solutions to overcome drug abuse and/or illicit trafficking so that overcrowding does not occur in the Class IIB Siborongborong Prison. This research is a holistic normative research, prescriptive analytical in nature, using normative methods, referring to legal norms contained in legislation. Data used as research supplements. This research uses the type of legislative regulatory approach, conceptual approach, and philosophical approach. Deductive qualitative analysis using Classical Economic Theory and Sociological Subcultural Pressure Theory, Legal Effectiveness Theory, and Benefit Theory as analytical tools. The results of the study concluded that there were 3 (three) factors causing the increase in the number of inmates related to the crime of drug abuse and/or illicit trafficking in Class IIB Siborongborong Prison. There were 2 (two) impacts of overcrowding in Class IIB Siborongborong Prison due to the increase in the number of inmates related to the crime of drug abuse and/or illicit trafficking. There were 7 (seven) solutions to overcome drug abuse and/or illicit trafficking so that overcrowding would not occur in Class IIB Siborongborong Prison.